Rozwiąż równanie.
a) 3(x - 5) + x = 2 - x
b) x + 2/3 + x = 3 - 2x
Wyznacz x z podanego wzoru.
a) xy = k, y = 0 (przekreślone =)
b) 4x + 2y = 6
c) a+b/x = 3, x = 0 (przekreślone 0)​


Odpowiedź :

rozwiąż

a) 3(x -5) + x = 2 - x

3x - 15 + x = 2 - x

4x - 15 = 2 - x

4x + x = 2 + 15

5x = 17 | : 5

x = 17/5 = 3 2/5

b) x + 2/3 + x = 3 - 2x

2x + 2/3 = 3 - 2x

2x + 2x = 3 - 2/3

4x = 2 1/3 | : 4

x = 7/3 * 1/4

x = 7/12

wyznacz x

a) xy = k | : y   y # 0

(y po lewej stronie się skróci)

x = k / y

b) 4x + 2y = 6

4x = 6 - 2y

x = (6 - 2y) : 4

x = 1,5 - 0,5y

c) a + b/x = 3, | * x  x#0

a+b = 3 * x | : 3

(po prawej 3 się skróci)

(a+b) / 3 = x

x = (a+b) / 3